Improvement of Community Welfare through Productive Zakat Empowerment (Case Study in KUA, Batanghari District, East Lampung Regency) - Muhamad Rudi Wijaya; Anas Habibi Ritonga (IAIN Padangsidimpuan, 2021)
Zakat is one of the pillars of Islam that every Muslim in the world must practice. Zakat works to reduce and eradicate problems. Poverty can be minimized or even eliminated by means of zakat. In addition, the optimization of productive zakat is needed to represent the realization of a prosperous society free of poverty. And productive Zakat is one strategy in community empowerment as a strategy for success in increasing community welfare. This study aims to determine the role of productive zakat in community empowerment to increase welfare. The research method used in this research is field qualitative. The results of research in improving welfare through productive zakat are carried out through 1. Program Planning, namely by budgeting the Activity Plan to the recipient, 2. Empowering implementation, namely giving zakat to mustahiq, implementing mentoring and mentoring as well as strengthening religious mentality for mustahiq, and 3.Evaluating activities empowerment, namely conducting a review for the recipient and returning it to a new mustahiq.